PENGARUH DISIPLIN KERJA TERHADAP KINERJA GURU DI SMP NEGERI 4 SUNGGUMINASA - Husnah, Asmaul; Tawe, Amiruddin; Kurniawan, Agung Widhi; Akbar, Abdi; Haeruddin, M. Ikhwan Maulana (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
The study aims to explore and analyze the relationship between work discipline and teacher performance at SMP Negeri 4 Sungguminasa. This research employs a quantitative correlation-based approach to investigate the impact of work discipline on teacher performance at SMP Negeri 4 Sungguminasa. The study involves a sample of 45 teachers, and data collection is conducted through questionnaires. The analysis methodology comprises validity and reliability tests, classical assumption tests, simple linear regression tests, and hypothesis testing (t-test). The findings demonstrate a significant and positive relationship between work discipline (X) and teacher performance (Y). The calculated regression coefficient for Work Discipline is 0.682 (positive), indicating a direct effect. This implies that a one-unit increase in work discipline corresponds to a 0.682-unit increase in teacher performance. In essence, higher work discipline among teachers at SMP Negeri 4 Sungguminasa leads to enhanced teacher performance, while lower work discipline is associated with decreased performance at the school.